Effect of rescanning with reduced interlayer times on microstructure and properties of titanium alloy via selective laser melting. (May 2022) - Ma, Yiqing; Wu, Meiping; Duan, Weipeng; Miao, Xiaojin; Li, Haohao; Han, Jitai
In the process of selective laser melting, laser rescanning technology is often used to optimize the residual stress and other properties of the formed parts. In order to improve the performance of parts and reduce the manufacturing time concurrently, this paper proposed a combined rescanning strategy. Based on finite element analysis, molten pool solidification behavior was simulated and studied. Ti6Al4V alloy samples were fabricated and analyzed by changing the rescanning strategies and process parameters. The microstructure, relative density, size of pore defects and residual stress were investigated under different rescanning strategies. It can be seen that the average cooling rate ranked in a descending order of SLM > re-SLM+IL1 > re-SLM, and samples formed by rescanning without layer interval had the best relative density and residual stress optimization effect, while the microstructure of each scanning strategy was all acicular α′ phase. When the number of rescanning interlayers and laser power was "one-layer" and 140 W respectively, the residual stress went down from 353 to 294 MPa. Finally, a simplified model was proposed to calculate the time cost for fabrication of rescanning with reduced interlayer times.